Are You Marrying Someone from a Different Culture or Religion? - Stephanie C. Toelle; Victor W. Harris (EDIS)
It was the author Paul Sweeney who penned, “A wedding anniversary is the celebration of love, trust, partnership, tolerance, and tenacity. The order varies for any given year.” Couples must make many adjustments as they learn to live with each other from year to year. When those adjustments include negotiating culture or religion, it adds another dimension to the process of trying to strengthen the relationship. This 7-page fact sheet was written by Stephanie C. Toelle and Victor W. Harris, and published by the UF Department of Family, Youth and Community Sciences, September 2012.